Morphological Development of the Particle -Վ- in the Armenian Language - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2024)
The study of the grammatical particle -վ- is of exceptional importance for a deep understanding of a number of realities of the morphological and syntactic system of the modern Armenian language. Professor Gurgen Sevak evaluates the expression of voice using the suffix –վ- as follows: “This is the most perfect way of expressing voice that the Armenian language has achieved in the new period of its development.” However, we have not fully studied the features of the origin and semantic-grammatical development of this particle. This article addresses these issues. The verb particle -վ- is formed from nouns and adjectives formed by the suffix -ուած (-ված). This spread widely in the Middle Armenian language, acquiring the meaning of the passive voice. In modern Armenian, this is the only and reliable indicator of the expression of the passive voice. At the syntactic level of the Armenian language, verbs with the passive particle -վ- form binomial (passive subject + predicate, expressed by a passive verb) and trinomial (subject + predicate + influencing object) passive structures that have unique semantic-functional and stylistic applications in various functional styles. The article also discusses the bigender characteristics of some of the passive verbs in the speech environment and the principles of their difference from verbs of a neutral gender.